Back Cover. (7th September 2020) - Wang, Haoyu; Yao, Jiejie; Zhu, Ying; Zhan, Weiwei; Chen, Xiaosong; Shen, Kunwei
Abstract : The cover image is based on the Original Article Association of sonographic features and molecular subtypes in predicting breast cancer disease outcomes by Haoyu Wang et al., https://doi.org/10.1002/cam4.3305 .